Technology-Mediated Sustainability of Organizational Change: Leadership Support and HR Capacity in Public Training - Jerry Marantika; Aldri Frinaldri; Retwando Retwando (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2026)
Sustaining organizational change following public-sector leadership training remains a major challenge, as post-training innovations frequently fail to become institutionalized due to leadership turnover and staff rotation. Although widely studied, empirical evidence explaining how leadership, human resources, and technology interact to sustain public-sector change remains limited. This study investigates the mediating role of Technology Utilization in the relationship between Leadership Support, Human Resource Capacity, and the Sustainability of Change Actions following the Administrator Leadership Training (PKA) at PPSDM Regional Bukittinggi, Indonesia. Using a quantitative explanatory design, data from 135 alumni were analyzed via Structural Equation Modeling Partial Least Squares (SEM-PLS). The results indicate that Technology Utilization significantly drives change sustainability (β = 0.421, p < 0.05) and mediates the effects of Leadership Support (β = 0.208, p < 0.05) and Human Resource Capacity (β = 0.180, p < 0.05). Conversely, direct effects of leadership and human resources were not statistically significant, demonstrating that sustainability relies on technology-enabled institutionalization rather than leadership or human capability alone. The model explains 75.2% of the variance in sustainability (R2 = 0.752). This study proposes the Technology-Mediated Sustainability of Change (TMSC) framework, extending Socio-Technical Systems Theory by positioning technology as the institutional mechanism transforming leadership support and human resource capacity into sustainable organizational practices. The findings offer practical guidance for government institutions and training providers to strengthen digital governance, knowledge management, and technology-enabled systems to ensure long-term change sustainability